Positioning Myself Between West and East - Shi, Xinnan (Stream: Interdisciplinary Journal of Communication, 2017)
Why would communications scholars want to present their positionality to the public? This was the first question I asked myself when I came across the term "positionality". Throughout my studies, I have approached communication as social science, and I have thought about communications researchers as scientists. I certainly understand that the objects of research in social science are social phenomena such as social relations and institutions, and that these are difficult to explain with quantitative data most of the time. But for me, being a scientist means holding back personal emotions and being objective in the production of knowledge about society. I believe that even a single case study should offer explanations not just of its immediate context, but also of broader social problems or phenomena.